Dynamic interactions between spatial change and travel behavior variation in old town fringe - Wenzhu Zhou; Qiao Li; Zhibin Li; Nan Wang; Qi Wang (Journal of Transport and Land Use, 2020)
Old town fringe area is changing in its spatial features, and these changes correspondingly result in variations in travel behaviors. Taking the spatial characteristics and travel behavior data of the Nanjing Old Town Fringe (OTF) area in 2010 and 2015 as an example, we conducted a comparative study for two years. First, based on the identification of the spatial range of OTF in these two years by using travel data mutation points and the Point of Information (POI) kernel analysis method, the significant change in the OTF area, from marginal areas in 2010 to non-marginal areas in 2015, was identified. Second, multiple logit models were used to evaluate the impact of the built environment and economic and social attributes of residents on the choice of travel modes, as well as the different impact factors. From the perspective of overall performance, with reference to the behavior of choosing motor vehicle travel, from 2010 to 2015, the significant correlation of factors in promoting residents to choose walking, cycling or public transit changed. Moreover, there were three different dynamic characteristics of this correlation change: (1) the correlation of factors was significant and stable from 2010 to 2015; (2) the correlation of factors was significant in 2010 but not significant in 2015; (3) the correlation of factors was not significant in 2010 but was significant in 2015. It was found that the correlated factors of fluctuation were mainly social attribute factors, for example, education, gender, age, whether having a driver’s license, etc. Therefore, in future research and practice, we need to focus on the impact of stable correlated factors (such as shortest distance to downtown, plot ratio, occupation, etc.) and factors with increasing correlations (such as bus coverage, gender, age, etc.). And the land-mix factor needs to be considered from both vertical and horizontal perspectives. This will have certain significance and help future development of OTF areas.